Jaminan dalam Pembiayaan Mudharabah (Studi Kasus Perbankan Syariah di Indonesia) (Sharia Faculty Islamic Economic Law Study Department, 2018)
Mudharabah transactions are currently included in the main elements of a fairly risky position, because even though this system takes place due to cooperation between sahibul mall and mudharib, the implementation is quite difficult. Moreover, the practice carried out in banking is not exactly the same as the system applied with the classical concept, coupled with the existence of several new provisions such as the implementation of collateral in the mudharabah financing contract.The purpose of this study is to find out analyzing the application of guarantees in mudharabah financing practiced by banks in Indonesia using the Islamic legal framework. The research method used in this study is descriptive-qualitative analysis. From this study it can be concluded that the application of guarantees in mudharabah financing in Islamic banks is absolutely required. Because the thing that becomes a special consideration is to avoid things that cause harm to one party. In this case an aspect of assymetric information which in this situation will create moral hazard.